ALASAN MERANTAUNYA ORANG MINANGKABAU DALAM KUMPULAN CERPEN PENGANTIN SUBUH KARYA ZULFEMI WIMRA (Tinjauan Sosiologi Sastra) - Rini Wirasty (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2020)
This study aimed to describe the causes of the Minangkabau people migrated in the short story collection Pengantin Subuh karya Zulfemi Wimra, many interesting things to study, especially regarding the causes of the Minangkabau people migrated. Short story is one form of literature that is used as a means of letters in raising issues relating to the causes wander. One of them is the short story works Zulfeni Wimra Bride dawn. The short story tells a lot about the causes wander in terms of sociology of literature. The method used in this study is a qualitative method that produces written data and events, about the shape of the causes wander in the short story collection The bride Dawn Wimra Zulfemi work. The technique used is descriptive, which is to describe in detail about the shape causes the Minangkabau people migrated in the short story collection The bride Dawn Wimra Zulfemi work. The results of this study causes Dawn Bride wander in the short story works Zulfemi Wimra as economic, social, educational, cultural and religious.